Pengaruh kepemimpinan dan iklim organisasi sekolah terhadap kinerja guru sma negeri 1 pasir penyu, air molek - Ferti, Marliani; Hendriani, Susi; Amsal, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of organizational climate variables and school leadership on teacher performance SMA 1 Negeri Pasir Penyu, Air Molek. As for the population in this study were all teachers of SMAN 1 Pasir Penyu, Air Molek which amounted to 56 people and the entire population sampled in this study using census method. The method of analysis used in this study is descriptive quantitative method, partial and simultaneous analysis (multiple linear regression analysis) with SPSS version 16. The results showed that there were significant and positive effect of the variables of leadership and school organizational climate, either simultaneously or partially, on teacher performance SMA 1 Pasir Penyu, Air Molek. Teacher performance SMA 1 Sand Turtle, Air Molek, 51.8% is determined by factors of leadership and school organizational climate, where the largest contribution is given by the variabel of leadership.Keywords: Leadership. school organizational climate and performance